Pengaruh Net Profit Margin dan Ukuran Perusahaan dalam Memprediksi Financial Distress pada Perusahaan Transportasi dan Logistik yang terdaftar di BEI Periode 2020-2024 - Andayani, Anastasia Puspitasari; Pramesti Dewi, Intan (Journal of Management and Bussines (JOMB), 2025)
This study aims to analyze the effect of Net Profit Margin (NPM) and company size (Size) on financial distress in transportation and logistics sector companies listed on the Indonesia Stock Exchange for the period 2020–2024. The research method used is descriptive verification with a quantitative approach. The purposive sampling technique was used to determine a sample of 27 companies during five years of observation, resulting in 135 observation data, but 85 data were analyzed after eliminating outliers. Data were obtained from the company's financial statements and analyzed using multiple linear regression with two prediction models: Zmijewski and Grover. The results showed that NPM had a negative and significant effect on financial distress based on the Zmijewski model, but showed a positive and significant effect in the Grover model. Company size did not show a significant effect in both models. The conclusion of this study emphasizes the importance of selecting a bankruptcy prediction model that is appropriate to the characteristics of the data, considering that each model has a different analytical approach to the same variable.   Keywords: Financial Distress, Net Profit Margin, Company Size